(untitled) - Omura, George (Indianapolis, Ind., 2006)
In this newest edition of his indispensable book, bestselling AutoCAD author and expert George Omura offers a practical and comprehensive guide to help you easily and efficiently learn the basics of AutoCAD. His straightforward explanations and task-based approach--thoroughly updated for AutoCAD 2007 and AutoCAD LT 2007--make this practical book more valuable than ever.
Keywords: Computer graphics,AutoCAD,Đồ họa máy tính,AutoCAD